Design and Development of a Phone Number–Based Anonymous Confession Application to Enhance Social Openness - Hilda Ashari; Muhammad Riska (Fakultas Teknik Universitas Negeri Makassar, 2026)
Social openness is a fundamental aspect of interpersonal communication; however, many individuals still struggle to express their thoughts and emotions due to social pressure and fear of negative judgment. This study aims to design and develop a phone number–based anonymous confession application as an alternative communication medium to enhance users’ social openness. The research adopts a Research and Development (R&D) approach using the Waterfall model, which includes requirement analysis, system design, implementation, testing, and maintenance. The application is developed using PHP and MySQL and evaluated based on the DeLone and McLean Information System Success Model, encompassing six dimensions, system quality, information quality, service quality, use/intention to use, user satisfaction, and net benefits. The study involves two system experts as validators and fifteen university students as respondents. The evaluation results indicate that the proposed application achieved an overall score of 94.31%, categorized as excellent. Specifically, system quality scored 95.56%, information quality 94.67%, service quality 95.11%, use/intention to use 92.67%, user satisfaction 92.67%, and net benefits 94.00%. These findings demonstrate that the application provides stable performance, relevant information, and responsive services. Furthermore, high levels of user engagement and satisfaction suggest that the system is user-friendly and effective in facilitating anonymous communication. In terms of impact, the application significantly improves communication comfort and promotes greater social openness. Therefore, the developed phone number–based anonymous confession application is considered a secure, effective, and practical alternative communication platform to support social openness in the digital era.